Implementation of Civil Procedural Law E-litigation in Justice System in Indonesia (Study in District Court in North Sumatra Region) - Abd Harris; Hani Ridho Nasution (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
The background of this research is because The Supreme Court has made a breakthrough in the Law administration of Cases in the Court Electronically (Online) by issuing Supreme Court Regulation (PERMA) Number 1 of 2019 concerning the Administration of Cases and Trials in The Court Electronically. The results of the research, the electronic trial system (e-Litigation) experienced many obstacles, especially in the district court area which is categorized, Blankspot area so that the trial process is not normal for example, the trial schedule that has been set in the e-Court can be known and cannot be known because of internet network interference such as in the Sibuhuan District Court area, Padang Lawas Regency, North Sumatra Province. This view was also affirmed by Abdullah Husain, an Advocate from Peradi Medan who had filed a case in the area. As a result, the Advocate had to contact the Substitute Registrar for the trial schedule to be reviewed because the internet network was problematic. In addition, people in the area prefer conventional (face-to-face) trials that have been carried out for decades on the basis of the law Rechtsreglemen buitengewesten (Rbg). The solution to this problem, the judges will generally question the litigants, whether the trial is electronic or not. The judge always gives views on this e-Court to the litigants in the courtroom, and if approved by all parties, news of the approval of the e-Litigation trial is made. The same obstacles are also experienced by the Simalungun/Pematangsiantar District Court, Padangsidempuan, Tebing Tinggi, Lubuk Pakam and Medan District Court. According to the e-Court Corner officer of the Medan District Court, Gunawan, in the Medan District Court there is very rare internet network disruption unless pln istric flow dies. Advocates take a better view with e-Litigation because the process is easier, faster, light and simple costs in accordance with Article 2 paragraph (4) of Law No. 48 of 2009 on Judicial Power. Of course also, also to avoid games by the judicial mafia. In addition, in the midst of the Covid-19 Pandemic condition is not over, PERMA No. 1 of 2019 will also help the parties not to flock to the conference. PERMA is strongly responded by advocates in Indonesia, especially in North Sumatra